Bioactive Secondary Metabolites: A Natural Blueprint Towards Therapeutic Approach - Amanpreet Kaur; Shubhangee Agarwal; Priyanka Rani; Pawan Kumar Shukla; Neha Bhatt (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
Secondary metabolites are a varied array of organic molecules synthesised by plants, microbes, and some animals that, while not directly associated with growth or reproduction, are essential for ecological interactions and defensive strategies. Compounds such as alkaloids, flavonoids, steroids, saponins, and terpenoids have attracted considerable interest owing to their broad uses in the medicinal, agricultural, cosmetic, and food sectors. Alkaloids are recognised for their strong pharmacological effects, flavonoids for their antioxidant capabilities, steroids for hormonal modulation, saponins for their antibacterial and immunomodulatory functions, and terpenoids for their extensive therapeutic potentials. Advancements in biotechnology, green chemistry, and artificial intelligence are transforming the discovery, extraction, and use of these natural compounds. Moreover, increasing environmental consciousness is propelling the transition to sustainable sourcing and manufacturing techniques. This chapter offers a comprehensive examination of the significance of secondary metabolites, addresses their many uses, and investigates future opportunities for their use in developing more sustainable and health-oriented solutions across several industries.